2008
DOI: 10.1007/s00428-008-0645-2
|View full text |Cite
|
Sign up to set email alerts
|

Asthma induction in mice leads to appearance of α2–3- and α2–6-linked sialic acid residues in respiratory goblet-like cells

Abstract: Allergic asthmatic inflammation in mice was induced by sensitization with ovalbumin and lipopolysaccharide from Escherichia coli and visualized in the airways of asthmatic mice by spatial and temporal changes of carbohydrates containing sialic acid residues. Immunohistochemistry was used to demonstrate binding of lectins and antibodies that detect alpha2-3- and alpha2-6-linked sialic acid residues. After sensitization and challenge, the histology of the lung changed markedly, and goblet-like cells appeared, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Increased detection of SNA staining in association with the presence of necrotic foci and viral antigen was observed in infected chickens. Local up-regulation of Siaα2-6 Gal glycotopes has been reported under different experimental inflammatory conditions [54][55][56]. For example, increase Siaα2-6 and Siaα2-3 glycotopes have been detected in respiratory cells of ferrets infected with H1N1 influenza virus [55], mice affected with asthma [54] and in serum of mice injected with turpentine oil to induce inflammation [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased detection of SNA staining in association with the presence of necrotic foci and viral antigen was observed in infected chickens. Local up-regulation of Siaα2-6 Gal glycotopes has been reported under different experimental inflammatory conditions [54][55][56]. For example, increase Siaα2-6 and Siaα2-3 glycotopes have been detected in respiratory cells of ferrets infected with H1N1 influenza virus [55], mice affected with asthma [54] and in serum of mice injected with turpentine oil to induce inflammation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Local up-regulation of Siaα2-6 Gal glycotopes has been reported under different experimental inflammatory conditions [54][55][56]. For example, increase Siaα2-6 and Siaα2-3 glycotopes have been detected in respiratory cells of ferrets infected with H1N1 influenza virus [55], mice affected with asthma [54] and in serum of mice injected with turpentine oil to induce inflammation [56]. Similarly, an increased expression of mRNA of α2-6 and α2-3 sialyltransferases have been observed in rat liver after inflammation [57], and human tracheal cells and bronchial mucosa stimulated with tumour necrosis factor-α (TNFα) [58].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical observation and experimental models described an enhanced level of total serum sialic acid and sialoglycans on the human vein endothelial cells as a marker of pathology and significant risk factor of coronary artery disease (CAD) and angiopathy [ 91 , 92 ]. Moreover, the glycome analysis in asthma and COPD showed that the alterations in sialoglycans correspond to the progress of disease [ 93 , 94 , 95 ]. According to Guo, the lung pathology inducing factors, e.g., tobacco, can be considered as the crucial players in the promotion of SARS-CoV-2 infection and associated with the risk of severe COVID-19 [ 95 ].…”
Section: Sialic Acids In Covs Infectionsmentioning
confidence: 99%
“…19 The two major secreted, gel-forming human airway mucins MUC5AC and MUC5B were reported to be elevated in chronic inflammatory airway diseases compared with healthy individuals, 8,[20][21][22][23][24] usually in an increased MUC5B/MUC5AC ratio. 1,21,25,26 In spite of the high diagnostic potential of the mucins, studies performed so far mainly focused on the general expression and localization of mucins, and did not provide specific data regarding whether the alterations observed were based on overproduction, modified distribution/composition or biochemical variations of one or more specific mucins.…”
Section: Introductionmentioning
confidence: 99%